Analysis of the Technological Feasibility of the Biodiesel Production Chain in the State of Ceará - Carmo, Breno Barros Telles do; Albertin, Marcos Ronaldo; Dutra, Nadja Glheuca Silva; Rodrigues, Maxweel Veras (Revista Gestão da Produção Operações e Sistemas, 2008)
The purpose of this study is to investigate the technological structure of the biodiesel productive chain (CPB) inCeará. The objective is, initially, to map the demands and technological offers of products, processes and management,identifying opportunities and challenges for regional development. The survey of information fromthis exploratory and descriptive study occurred through technical visits, literature, participation in seminarsand conferences, and interviews with entrepreneurs and researchers. The major technology gaps and opportunitieswere identified for each link of the CPB, from the process of planting and managing the product and itscrushing to the refinement of the biodiesel. The greatest needs encountered included, the need for technologicalmanagement in companies that manufacture equipment, lack of agribusiness skills and in the associations offamily farming to manage the micro power plant crushing and refinement, technologies to add value and applyco-products as well as the lack of mamona as a raw material. Overcoming these technology gaps will contributeto the sustainable development of CPB, mitigating the environmental and socioeconomic problems of theState and promoting economic inclusion of thousands of families in the semi-arid northeast.Keywords: Productive chain. Biodiesel. Demands and Technological Offers